Oral Fixation or Oral Corrective? A Response to Larry Hurtado. (29th February 2016) - Iverson, Kelly R.
Abstract : Over the last several decades, performance criticism has made significant headway as an interpretive method. However, in a recent issue of this journal, Larry Hurtado argues that the key assumptions of the movement ignore various historical realities regarding the use of texts in the ancient world. The following discussion offers a brief response to what Hurtado suggests are several 'oversimplifications'. The essay argues that rather than being a 'fixation' as Hurtado maintains, the renewed focus on orality and performance is a corrective that helps to provide a broader understanding of how biblical texts were typically experienced in the ancient world.